PENINGKATAN KECERDASAN VISUAL SPASIAL ANAK USIA DINI MELALUI METODE PEMBELAJARAN LOOSE PART DENGAN MENGGUNAKAN BAHAN ALAM DI TK NEGERI BANTEA - Akbar, Muhammad; Maronta, Yusuf; Zanurhaini, Zanurhaini (MAANA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to improve the visual-spatial intelligence of early childhood through the loose part learning method using natural materials at Bantea State Kindergarten. Visual spatial intelligence is the ability of children to recognize, organize, and arrange visual elements into meaningful forms. This study is a classroom action research (CAR) conducted in two cycles with stages of planning, implementation, observation, and reflection. The research subjects consisted of 11 children at Bantea State Kindergarten. Data was collected through observation using visual-spatial assessment sheets based on child development indicators. The results of the study showed that there was an improvement in each cycle. In the pre-cycle stage, only 2 children (18.18%) reached the Developing as Expected (DAE) category. After implementing the loose parts method using natural materials in the form of collages, the number of children who reached the DAE category increased to 4 children (36.36%) in cycle I, and increased significantly to 8 children (72.73%) in cycle II. In the pre-cycle stage, the majority of children were still in the Not Yet Developing (NYD) and Beginning to Develop (BD) categories. After receiving intervention in cycle I and refinement in cycle II, there was a significant increase in the number of children who reached the Developing as Expected (DAE) category. In cycle II, 8 children (72.73%) successfully demonstrated visual-spatial abilities in line with developmental indicators, while the number of children in the ND category decreased to only 1 child (9.09%). This increase shows that loose part-based learning with natural materials can provide appropriate stimulation for children in developing an understanding of the concepts of shape, color, size, direction, and patterns. Additionally, this activity also provides space for children to express themselves freely, improve concentration, and strengthen eye coordination. It can be concluded that the application of the loose parts learning method using natural materials is effective in improving the visual-spatial intelligence of early childhood. Learning designed through exploratory activities such as arranging, sticking, and rearranging objects made from natural materials (grains) encourages children to develop visual perception, spatial skills, and creative and logical thinking. These activities allow children to explore, recognize shapes, patterns, and spaces, and encourage them to think creatively through enjoyable hands-on experiences.